Studi Literatur: Peran Guru Penggerak Dalam Rangka Peningkatan Kualitas Pendidikan Nasional - Palobo, Agri Felisitas; Yoenanto, Nono H (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
This research aims to describe the role of driving teachers in efforts to improve the quality of national education. The method used is a literature review study method from 12 sources consisting of 3 books and 9 journals from Google Play Books, Google Scholar, and Research Gate using the keywords